A short review of working memory and attention in depression - Siti Atiyah, Ali; Nor Asyikin, Fadzil; Tahamina, Begum; Faruque, Reza; Faiz, Mustafar; Humaira, Nisar (International Research Center for Cognitive Applied Neuroscience (IrcCAN), 2024)
A neuropsychological evaluation provides comprehensive insights into children’s neurocognitive function. This study assessed learning disability performance in children through neuropsychological assessment, examining cognitive profiles and emotionalbehavioural functioning. The data from 271 respondents using self-administered questionnaires, explored mindfulness-based interventions to address cognitive skills, emotional regulation, and academic performance. Employing a quantitative approach with structural equation modelling and SPSS analysis, we found a significant relationship between children’s emotional-personality behavior and learning disabilities. The regression analysis indicated a negative impact on cognitive ability and learning disability, suggesting reduced motivation to learn. This study highlights the importance of neuropsychological assessment in understanding and addressing learning disabilities in children, influencing their socialization and adjustment in educational settings. It underscores the significance of such assessments in enhancing educational outcomes for children facing learning challenges.